"Rhodes‐" must fall: Some of the consequences of colonialism for botany and plant nomenclature. Issue 1 (28th October 2021) - Smith, Gideon F.; Figueiredo, Estrela
Abstract: A recent increase in awareness of the impact and aftereffects of imperialism and colonialism has served to indicate to the world that change can occur rapidly and likely irreversibly in numerous spheres of life. A well‐publicised example is the "Rhodes Must Fall" campaign that started in Cape Town, South Africa, in 2015, and eventually spread to the United Kingdom. One of the outcomes of this initiative has been the removal of the statue of Cecil John Rhodes from the campus of the University of Cape Town. Yet, in plant nomenclature, because of the rules that govern the scientific naming plants, names that include the root " rhodes ‐", where C.J. Rhodes is commemorated, are persisting. This is one example of names and epithets that are perceived by many as offensive and unacceptable. The botanical community should take cognisance of these developments and use the mechanisms at its disposal, or develop new ones, to proactively find solutions to address how to deal with such names and epithets.